Development of SETS Based E-book Teaching Materials in Strengthening Science Literacy in Elementary School - Febrianti, Retno; Prasasti, Pinkan Amita Tri; Kusumawati, Naniek; Irawan, Nico (IJECA (International Journal of Education and Curriculum Application), 2022)
This study aims to produce one of the teaching materials that can be used for elementary school students to strengthen scientific literacy. The research method used is Research and Development (R&D), the subjects in this study were the 18th graders of SDN Pilangbango. Data collection techniques using observation, questionnaires and documentation. The results achieved in this study are developing SETS-based E-book teaching materials and testing the feasibility of the validation results of experts, teacher and student responses get a percentage of linguists 86%, material experts 82%, media experts 100%, student responses were 91.89%, teacher responses were 94% and got the criteria "very valid". So it can be concluded that this study resulted in a SETS-based E-book teaching language that was able to strengthen the scientific literacy of grade VI elementary school students who had been tested. By experts who get very valid eligibility criteria.